Following an Uneven Lead: Trickle-Down Effects of Differentiated Transformational Leadership - Bormann, Kai C.; Diebig, Mathias (Journal of Management, 2021)
Drawing from conservation-of-resources theory, we examine a trickle-down model of differentiated transformational leadership (leaders treating followers differently) across three hierarchical levels (i.e., managers, supervisors, and supervisors’ followers). Specifically, we develop a model in which manager differentiated transformational leadership increases department unit stress (i.e., the managers’ group of followers), which then translates into increased differentiated supervisor transformational leadership. The latter then again positively predicts team unit stress (i.e., the supervisors’ group of followers) and, eventually, results in decreased team helping behavior of supervisors’ followers. We tested this model using data from a large, multisource field study. The results provide support for our trickle-down model in that department managers’ differentiated transformational leadership decreased team helping behavior two hierarchical levels below the manager via increasing department unit stress (Stage 1 mediator), supervisor differentiated transformational leadership (Stage 2 mediator), and team unit stress (Stage 3 mediator).